SISTEM PENGAMANAN PENGINPUTAN NILAI DOSEN PADA SISTEM INFORMASI AKADEMIK BERBASIS SMS - Asnurul Isroqmi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Academic information systems in universities are very important for academic activities of lecturers and students who are so dynamic, but this is meaningless if it is not supported by a good level of security of the system itself, especially for lecturers who are unfamiliar with mastering Information Technology. One of the important things in academic information systems is when inputting student grades at the end of the semester, it is necessary to have a security system that can be controlled by the lecturer himself even though the lecturer does not really control information technology. The innovation in making the One Time Password (OTP) feature that is sent to the user's lecturer cellular phone through Short Message Service (SMS) when value is collected, is a simple but reliable security system. This study aims to discuss the application of security to access the WEB-based Academic Information System when lecturers make inputting scores, in the form of security using One Time Password generated from random programs and MD5 hashes that generate an SMS code for authentication.